Leakage Current Mitigation in On-Grid Photovoltaic Systems Using a Flexible Multi-Level Inverter Topology - Caíque C. A. de Carvalho; Paulo R. D. R. da Silva; José M. Araújo; José A. Pomilio (Eletrônica de Potência)
Leakage current is an issue that often causes problems in transformerless grid-connected PV inverters, such as electromagnetic interference, which is conducted or radiated and derates the quality of power injected into the grid. It can also lead to electrical safety problems, impair the performance of other equipment nearby, and thus make the generation system unavailable. Therefore, mitigation procedures for the leakage current in transformerless grid-connected PV inverters are essential to ensure system efficiency and safety. In this sense, a new single-phase grid-connected transformerless inverter topology was proposed using modulation switching techniques to keep the leakage current at acceptable standard levels. With the proposed topology, by monitoring the leakage current rms value, the inverter can be driven in a three- or five-level pattern for the main switches, thereby keeping the leakage current at a satisfactory level. The topology was implemented in a versatile hardware-in-loop Typhoon-HIL to emulate a digital twin of the complete system, with the control loops and switching generation embedded in a family Texas Instruments F28335 DSP. The results obtained for total harmonic distortion and energy conversion efficiency were then compared with other consolidated topologies, and the leakage current was proved to be effectively modified when the inverter is switched in three- or five-level modes.